2018
DOI: 10.1262/jrd.2018-080
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the antral follicle count in bovine ovaries from a local abattoir and steroidogenesis of granulosa cells cultured as oocyte-cumulus-granulosa complexes

Abstract: The antral follicle count (AFC) is used as an indicator of cow fertility. We herein investigated the relationship between AFC and the steroidogenesis of granulosa cells and confirmed the developmental competence of oocytes derived from early antral follicles (0.5-1.0 mm) using in vitro growth culture. Slaughterhouse-derived ovaries were divided into high (≥ 25) and low (< 25) AFC groups based on AFC (≥ 2.0 mm). Oocyte-cumulus-granulosa complexes (OCGCs) collected from early antral follicles were cultured for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…The antral follicle count (AFC) is used commonly as an indicator of cow fertility and according to Ireland et al and the number of follicles positively correlated with the development rate of blastocysts [38,39]. These data are in agreement with our results because the nearest number of follicles and oocytes we received from pregnant hinds, as donor of oocytes, and further the development rate in this experimental group was the lowermost.…”
Section: Discussionsupporting
confidence: 90%
“…The antral follicle count (AFC) is used commonly as an indicator of cow fertility and according to Ireland et al and the number of follicles positively correlated with the development rate of blastocysts [38,39]. These data are in agreement with our results because the nearest number of follicles and oocytes we received from pregnant hinds, as donor of oocytes, and further the development rate in this experimental group was the lowermost.…”
Section: Discussionsupporting
confidence: 90%
“…Cumulus cells play an important role during oocyte growth and maturation, among them supply nutrients [ 14 ] and to mediate the effects of hormones during oocyte maturation [ 15 ]. Mingoti et al [ 16 ] demonstrated that CCs of bovine COCs can secrete E 2 and P 4 in maturation media, and Endo et al [ 17 ] and Sakaguchi et al [ 18 ], demonstrated that exogenous and endogenous E 2 by granulosa cells directly supports the in vitro development of bovine COCs. In the present study, supplementation with 25 and 50 μM nobiletin in maturation medium increase in E 2 and P 4 production by CCs.…”
Section: Discussionmentioning
confidence: 99%
“…We have also tried to develop the in vitro growth (IVG) culture system for bovine small-sized oocytes (approximately 95 µm in diameter), which have no developmental competence without IVG [36,37,38,39,40,41,42,43,44,45]. In these studies, we attempted the pre-IVM culture of oocytes using IBMX after 12- or 14-day IVG culture [36, 37].…”
Section: Studies On the Improvement Of Oocyte Developmental Competencementioning
confidence: 99%
“…Our ultimate objectives are to establish the model of in vivo follicular development and to produce the oocytes with high developmental competence the same as in vivo matured (ovulated) oocytes; however, cultured oocyte-granulosa-cumulus complexes produce a large amount of progesterone during IVG like as degenerating follicles [41,42,43]. It means that the IVG system can be used as the model of degenerating follicles but not healthily developing follicles.…”
Section: Studies On the Improvement Of Oocyte Developmental Competencementioning
confidence: 99%